Visible‐to‐Ultraviolet Light Conversion: Materials and Applications. Issue 6 (1st May 2021) - Du, Yangyang; Ai, Xiangze; Li, Ziyu; Sun, Tianying; Huang, Yang; Zeng, Xierong; Chen, Xian; Rao, Feng; Wang, Feng
Abstract : Photon frequency conversion using optical materials is a common strategy for light generation and utilization. Materials capable of visible‐to‐ultraviolet (UV) light conversion have attracted particular attention due to their potential applications in nonlinear optics, biophotonics, as well as environmental sciences. There are four main mechanisms of visible‐to‐UV light conversion processes, including second‐harmonic generation, two‐photon absorption, lanthanide‐based upconversion, and triplet–triplet annihilation. Herein, recent developments in visible‐to‐UV light conversion materials are collectively reviewed and the emerging applications are presented. The prospects and challenges for further development in this field are also highlighted. Abstract : Recent advances in visible‐to‐ultraviolet (UV) light conversion are discussed herein. Developments in optical for second‐harmonic generation, two‐photon absorption, lanthanide‐based upconversion, and triplet–triplet annihilation are reviewed. Application of these materials in UV lasers, microbial inactivation, and photoredox catalysis are discussed. Challenges for further development are also highlighted.